2016
DOI: 10.3390/s16122207
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Depth Profiling into Biotissues Using Micro Electrical Impedance Spectroscopy on a Needle with Selective Passivation

Abstract: A micro electrical impedance spectroscopy (EIS)-on-a-needle for depth profiling (μEoN-DP) with a selective passivation layer (SPL) on a hypodermic needle was recently fabricated to measure the electrical impedance of biotissues along with the penetration depths. The SPL of the μEoN-DP enabled the sensing interdigitated electrodes (IDEs) to contribute predominantly to the measurement by reducing the relative influence of the connection lines on the sensor output. The discrimination capability of the μEoN-DP was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 39 publications
(40 reference statements)
0
20
0
Order By: Relevance
“…Previous work with bipolar systems report impedance changes as a function of probe insertion depth (Bolger et al 2006, Yun et al 2016. To minimize this depth dependence, a 15 μm thick diamond-like carbon (DLC) coating (IBC Coatings Technologies, Lebanon, IN) was applied to the surface of a standard 2 mm cannulated twist drill (Type 36117, Nobel Biocare, Kloten, Switzerland) everywhere except the distal 2 mm and within the cannula via a Plasma Assisted Chemical Vapor Deposition (PACVD) process.…”
Section: Device Developmentmentioning
confidence: 99%
“…Previous work with bipolar systems report impedance changes as a function of probe insertion depth (Bolger et al 2006, Yun et al 2016. To minimize this depth dependence, a 15 μm thick diamond-like carbon (DLC) coating (IBC Coatings Technologies, Lebanon, IN) was applied to the surface of a standard 2 mm cannulated twist drill (Type 36117, Nobel Biocare, Kloten, Switzerland) everywhere except the distal 2 mm and within the cannula via a Plasma Assisted Chemical Vapor Deposition (PACVD) process.…”
Section: Device Developmentmentioning
confidence: 99%
“…Depending on the technique, the needles must either be directed to their target position or kept on a straight path to improve the targeting precision and hence quality of care. measurements [25,26]. An impedance measurement analyzer with an injectable monopolar needle electrode has been used in various clinical fields for tissue biopsy, peripheral intravenous catheterization and lumbar puncture.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies have determined the electrical impedance of organic cells using electrochemical impedance spectroscopy [30,31]. The EIS-on-a-needle (EoN) technique can calculate the electrical impedance dependent on an electrochemical system, for example, the electrical properties of the sample, and the constant phase element (CPE) on the surface near to the electrodes [26,32]. EoN consists of two main components, a connection part and a detection part.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To accurately detect the needle position in vivo, electrical impedance characterization of tissues can be applied, which non-destructively measures in real-time the electrical properties of the tissue by using a weak alternating electric field [4,5]. Kalvøy et al reported the feasibility of the needle guidance in clinical applications using the finite element method (FEM) simulation of electric fields to the electrical impedance (EI) measurement on tissues [6].…”
Section: Introductionmentioning
confidence: 99%